Polyoxometalate-Assisted Layered Double Hydroxide for Facile Photocatalytic Methylene Blue and Malachite Green - Hanifah, Yulizah; Ahmad, Nur (Science and Technology Indonesia, 2025)
To increase the photodegradation activities of polyoxometalate, the co-precipitation approach has been used to prepare intercalated polyoxometalate compounds with ZnAl-LDH on methylene blue and malachite green dye. It is strongly advised to use the preparation catalyst LDH with polyoxometalate to create a successful method for anionic dye reduction. This study demonstrated the effectiveness environmentally method for intercalating ZnAl_LDH with polyoxometalate compound by employing methylene blu and malachite green dye as an organic pollutant. Additionally, the results showed that for pH = 7 for ZnAl- SiW12O40 on degraded malachite green, and the highest researching 94% on degradation methylene blue on ZnAl-PW12O40. Due to the rapid dissociation of the procion red reduction from the polyoxometalate photocatalytic activities, it was thought to have significant co-catalyst effects.